Neutrophil-Lymphocyte Ratio (NLR) as a Prognostic Marker in Advanced Lung Cancer Patients Undergoing First-Line Treatment - Dewi, Dinda Ary Miranda; Setyawan, Ungky Agus; Karliasari, Liana (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Neutrophil-lymphocyte ratio (NLR) is one of the systemic inflammatory markers that play a role in detecting the degree of sepsis in the cancer microenvironment. A high NLR, with a dominant predominance of neutrophil cells, can release cytokines and chemokines that induce cancer cell proliferation and metastasis. Conversely, a low NLR, predominately of lymphocyte cells, can activate the immune system to handle chronic inflammation. From its mechanism of action, NLR is often used to predict the future prognosis and survival rate of cancer patients. This study aimed to analyze the effect of first-line therapy in lung cancer patients with an alternative prognostic indicator in the form of changes in NLR values confirmed by the response evaluation criteria in solid tumors (RECIST). Methods: This study used an analytical observational method with a cross-sectional approach and was conducted using secondary data samples from the medical records of lung cancer patients treated at Dr. Saiful Anwar General Hospital, Malang. Results: Spearman’s correlation analysis between NLR and RECIST revealed a relationship (p = 0.001). Determining the NLR cut-off point using the receiver operating characteristic (ROC) curve yielded a value of 3.55, with NLR sensitivity and specificity at 69.44% and 69.76%, respectively. The therapy administration to lung cancer patients significantly decreased NLR (p = 0.032). Conclusion: NLR is a valuable tool for routinely monitoring therapy outcomes in lung cancer patients and can be considered an alternative prognostic marker due to its promising results.